Observation of Food Handlers’ Hand Hygiene Behavior During Production at a Sandwich-making Factory - Abuzar I.A. Mohamed; Ellen W. Evans (Journal of Food Protection)
Effective hand hygiene is essential during food production to reduce the risk of microbiological contamination. Improper hand hygiene by food handlers can be a major contributing factor in the spread of foodborne illnesses. Self-reported behavior does not equate to actual behavior as it has the limitation of biases. Therefore, observational data are more effective at assessing the actual behavior of food handlers. Covert observation utilizing closed-circuit television (CCTV) cameras can yield reliable data. This study utilized covert observation to assess hand hygiene compliance from CCTV footage of food handlers in a sandwich-making facility. An electronic observation checklist, based upon the company’s hand-hygiene protocol, was used to capture observed hand hygiene practices. A total of 588 occasions that required hand hygiene practices by food handlers (n = 12) were observed during the production of ready-to-eat (RTE) sandwiches over 16 h during two shifts. Food handlers did not wash their hands on 32% of occasions which required food hygiene practices. Of those occasions where there was an attempt to implement hand hygiene practices (n = 401), only 1% of behaviors were compliant with the company hand hygiene protocol. Observations indicated that 95% of attempts did not adhere to the recommended handwashing duration (≥20 s). Soap was not used in 4% of attempts, and hands were not wetted prior to applying soap in 16% of attempts. Additionally, 62% of attempts did not use hand sanitizer after handwashing and drying. Food handlers were observed attempting hand hygiene practices significantly more frequently (p < 0.001) when entering (89% of occasions) than exiting (8% of occasions) the production area. Findings indicate that appropriate interventions are needed to improve hand hygiene compliance of food handlers to ensure food is produced safely within the food manufacturing sector.